2014
DOI: 10.1094/phyto-04-13-0110-r
|View full text |Cite
|
Sign up to set email alerts
|

Population Structures of ‘Candidatus Liberibacter asiaticus’ in Southern China

Abstract: Huanglongbing (HLB) is a highly detrimental citrus disease associated with 'Candidatus Liberibacter asiaticus', a nonculturable alpha-proteobacterium. Characterization of the bacterial populations is important for development of disease management strategies. In this study, the 'Ca. L. asiaticus' populations in eight provinces in southern China where HLB is endemic were analyzed based on tandem repeat number (TRN) variations in a previously characterized genomic locus CLIBASIA_01645. Of the 224 HLB samples col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 12 publications
1
18
0
2
Order By: Relevance
“…TRN in genomic loci like CLIBASIA_01645 is more precise in genetic differentiation of CLas isolates in comparison to single nucleotide polymorphisms (Katoh et al, 2011). The amplification of CLIBASIA_01645 loci of CLas strains from NEH region in present study revealed that all the strains belonged to single amplicon group (SAG) exhibiting identical electrophoretic profile as reported previously (Chen et al, 2010; Ma et al, 2014). Association of specific TRN class of CLas genotype with specific citrus cultivar has been observed e.g.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…TRN in genomic loci like CLIBASIA_01645 is more precise in genetic differentiation of CLas isolates in comparison to single nucleotide polymorphisms (Katoh et al, 2011). The amplification of CLIBASIA_01645 loci of CLas strains from NEH region in present study revealed that all the strains belonged to single amplicon group (SAG) exhibiting identical electrophoretic profile as reported previously (Chen et al, 2010; Ma et al, 2014). Association of specific TRN class of CLas genotype with specific citrus cultivar has been observed e.g.…”
Section: Discussionsupporting
confidence: 85%
“…Current study indicated that inter-population TRN distribution in the different citrus groves of India is different. The CLas strains from North East India belonged to SAG as like that of Guangdong and Florida (Chen et al, 2010) unlike that of existence of both SAG and multiple amplicon group reported from Southern China (Ma et al, 2014). …”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations